STUDY OF FUNCTIONAL INDICATORS OF YOUNG SWIMMERS - Gofurov Abduvokhid Makhmudovich; Gofurov Abdushokir Makhmudovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the process of selection in swimming, orientation is aimed at choosing a sports method of swimming, the structure of long-term training, as well as the content of training loads, taking into account the individual characteristics of the athlete’s fitness and competitive activity.